Cost and contract administration in construction: divine perspectives - Ayob, Mohd Fairullazi (IIUM Press, 2016)
This book is a compilation of 8 papers that separated into two parts, i.e. Part 1- Construction Cost, and Part 2- Contract Management. Each part reflects the focus and contents of the paper and the authors’ endeavour to address some of the current issues in the building construction